Litter and air quality in different broiler housing conditions - de Carvalho, Thayla Morandi Ridolfi (2011)
The objective of this work was to assess the initial conditions of poultry housing for one‑day‑old chicks regarding the quality of reused bedding and of the air in commercial broiler houses with different types of minimum ventilation and typology, using geostatistical analysis. The experiment was carried out in four broiler houses: Blue House I (T1) and Blue House II (T2), Dark House (T3), and Conventional (T4). The following variables were evaluated: pH, moisture, surface temperature, and ammonia concentration, and samples were collected at bird height at 80 equidistant points in the brooding areas. Geostatistical analysis helped to identify the environmental critical control points. The management of minimum ventilation is not sufficient to guarantee air quality in the brooding area. The reused coffee and rice husk beds (T1 and T2) show better quality than the reused wood shaving beds (T3 and T4). The minimum ventilation system, in T2 and T4, is the most efficient regarding air renovation inside the brooding areas.